2022
DOI: 10.1101/2022.07.11.499650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechano-epigenetic regulation of extracellular matrix homeostasis via Yap and Taz

Abstract: Cells integrate mechanical cues to direct fate specification to maintain tissue function and homeostasis. While disruption of these cues is known to lead to aberrant cell behavior and chronic diseases, such as tendinopathies, the underlying mechanisms by which mechanical signals maintain cell function is not well understood. Here, we show using a novel model of tendon de-tensioning that loss of tensile cues in vivo acutely changes nuclear morphology, positioning, and expression of catabolic gene programs. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 44 publications
6
11
0
Order By: Relevance
“…The copyright holder for this preprint this version posted September 16, 2022. ; https://doi.org/10.1101/2022.09.13.507820 doi: bioRxiv preprint fibronectin whose production is regulated by estrogen signaling 30,31 , in female MRL/MpJ tendons compared to male MRL/MpJ tendons during the proliferative phase of wound healing. Jones et al 32 recently reported a mechanoregulatory mechanism wherein elevated YAP/TAZ signaling suppresses catabolic gene expression that corroborates our in vitro and in vivo findings. Furthermore, our group and others have postulated a role for cellular protrusion dynamics in sensing and responding to changes in mechanical loading that subsequently drives cytoskeletal and ECM reorganization 23,33 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted September 16, 2022. ; https://doi.org/10.1101/2022.09.13.507820 doi: bioRxiv preprint fibronectin whose production is regulated by estrogen signaling 30,31 , in female MRL/MpJ tendons compared to male MRL/MpJ tendons during the proliferative phase of wound healing. Jones et al 32 recently reported a mechanoregulatory mechanism wherein elevated YAP/TAZ signaling suppresses catabolic gene expression that corroborates our in vitro and in vivo findings. Furthermore, our group and others have postulated a role for cellular protrusion dynamics in sensing and responding to changes in mechanical loading that subsequently drives cytoskeletal and ECM reorganization 23,33 .…”
Section: Discussionsupporting
confidence: 90%
“…Jones et al . 32 recently reported a mechanoregulatory mechanism wherein elevated YAP/TAZ signaling suppresses catabolic gene expression that corroborates our in vitro and in vivo findings. Furthermore, our group and others have postulated a role for cellular protrusion dynamics in sensing and responding to changes in mechanical loading that subsequently drives cytoskeletal and ECM reorganization 23,33 .…”
Section: Discussionsupporting
confidence: 89%
“…In addition to MRTF, the presence of F-actin stress fibers has also been shown to be associated with nuclear YAP. In support of the gene regulation by YAP, a recent study determined that small interfering RNA knockdown of Yap increases the expression of Mmp-3 and Mmp-13, while overexpression reduces these levels ( Jones et al. , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 20,62,69 ] Thus, beyond recreating the anisotropy and the specific biochemical cues of native tendon tissues, this strategy allows to provide cells with dynamic mechanical stimuli, which are known to promote the tenogenesis of stem cells and maturation of bioengineered tendon constructs. [ 70–73 ]…”
Section: Resultsmentioning
confidence: 99%
“…[20,62,69] Thus, beyond recreating the anisotropy and the specific biochemical cues of native tendon tissues, this strategy allows to provide cells with dynamic mechanical stimuli, which are known to promote the tenogenesis of stem cells and maturation of bioengineered tendon constructs. [70][71][72][73] To test the effectiveness of our system in delivering mechanical stimuli to encapsulated hASCs, we first evaluated the cellular localization of YAP (Yes-associated protein) and TAZ (transcriptional coactivator with PDZ binding motif ), two key proteins in the mechanotransduction pathways. YAP/TAZ is predominately cytoplasmic, but upon activation they translocate to the nucleus, where they regulate the expression of different mechanosensitive genes.…”
Section: Tendon Decm Microfibers Alignment Directs Adipose Stem Cells...mentioning
confidence: 99%